Pengaruh Sport Massage terhadap Fleksibilitas Otot dan Ambang Nyeri Otot Hamstring pada Atlet Kabaddi Surabaya - Muhammad Sulthoni Puruso Nindyo; Joesoef Roepajadi; Dita Yuliastrid; Muhammad Dzul Fikri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Kabaddi is a traditional outdoor game played with slight variations across India. Prevention of hamstring injuries in kabaddi athletes requires a multifaceted approach, including a balanced muscle strengthening program, regular flexibility training, thorough warm-up before the match, and adequate recovery after intense activity. This study aims to analyze the effect of sports massage on muscle flexibility and pain threshold in the hamstring muscles of Surabaya Kabaddi athletes. The research method used was quantitative with a pretest-posttest design in two groups, namely the experimental group given sports massage intervention and the control group. The sample in this study was 12 Surabaya Kabaddi athletes who were divided into 2 groups, namely the treatment group and the control group using the Total Sampling technique. The results of the Paired t-test showed that there was a significant effect on the hamstring muscles after being given sports massage and a decrease in the pain threshold in the experimental group compared to the control group, as evidenced by the results of the t-test which showed a significant value <0.05. It can be concluded that sports massage can have an effect on hamstring muscle flexibility and pain threshold.